O004 Blood group antigen removal of a human kidney using ex-vivo normothermic machine perfusion technology. (22nd July 2022) - MacMillan, S; Hosgood, SA; Nicholson, ML
Abstract: Introduction: A novel strategy to overcome the constraints of ABO compatibility in solid organ transplantation is the enzymatic removal of blood group antigens using an alpha-galactosidase enzyme from Bacteroides fragilis during ex-vivo normothermic machine perfusion (NMP). Methods: Human kidneys rejected for transplantation and offered for research were used in this study which was approved by the National Research Ethics committee and Research and Development office (NRES: 15/NE/0408). Blood group antigen removal using the alpha-galactosidase enzyme GH110B from B. fragilis was first investigated on formalin-fixed paraffin-embedded (FFPE) cortex sections from human kidneys of blood group B (n=5). Immunofluorescence co-staining of the blood group B antigens (isolectin GSIB4) and vascular endothelium (CD-31) was completed. A human kidney of blood group B was then treated with 0.0025mg/ml of alpha-galactosidase during 6hrs of NMP using an acellular perfusate solution. Serial biopsies taken throughout perfusion were stained and analysed for antigen removal. Results: Alpha-galactosidase treatment of FFPE sections at all concentrations examined (0.0013mg/ml 0.5mg/ml) caused significant reduction of the Pearson correlation coefficient for B antigen and CD-31 co-localisation compared to the untreated control (p<0.001). Following NMP of the treated B kidney, the Pearson correlation coefficient dropped from 0.182±0.042 (pre-treatment level) to a minimum of 0.017±0.102 after 6hrs (p<0.0001), indicating a near-complete loss of the blood group antigens. Conclusion: This is the first example of the enzymatic removal of type B blood group antigens from a human kidney during NMP. This strategy may have the potential to increase the pool of ABO compatible donor kidneys for transplantation. Take-home message: We have shown that an alpha-galactosidase enzyme added during ex-vivo normothermic machine perfusion can be used to enzymatically remove the blood group B antigens from human kidneys, providing the first example of whole organ conversion in humans. This strategy has the potential to massively increase the pool of ABO compatible donor kidneys for transplantation.